Youtube e surdez: análise de discursos de surdos no ambiente virtual - Festa, Priscila Soares Vidal (2012)
Currently, YouTube has dominated the segment of online videos in the world, and in Brazil it is no different. Due to the site's visibility, YouTube can be looked as a possibility of expression for a person that is deaf, as it allows discourses, made in sign language, to be registered. This study has the objective of analyzing the discourses produced by deaf people and posted on YouTube regarding the themes deaf culture, aspects of the living environment between hearing and deaf and political manifestations. This study's content was composed by 25 videos in which the deaf people manifested themselves about deafness. The study offered us data and conditions to consider YouTube as a tool to provide deaf people a new interactive space in their discursive production by establishing interaction. In light of Bakhtin's theory of language, it was possible to identify the social voices present in the discourses as well as the change in otherness, dialogic, enunciation, heteroglossia and responsiveness. With this study, it became possible to conclude that, on behalf of YouTube, deaf people where able to establish a reason to value "being deaf", which presents the possibility of reconstructing, through sign language, a new opinion about deafness.